Reducing the Ciphertext Size of Dolev-Dwork-Naor like Public Key Cryptosystems - Dowsley, Rafael; Hanaoka, Goichiro; Imai, Hideki; Nascimento, Anderson C. A. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2010)
We show a method for compressing the ciphertext and reducing the computational cost of the Dolev-Dwork-Naor cryptosystem and related schemes without changing their other parameters nor reducing the original security levels.